Pengaruh Shopping Lifestyle dan Diskon Terhadap Impulse Buying di E-commerce Shopee Pada Mahasiswa UPN “Veteran” Jawa Timur - Putri Agustin Dwi Ningrum; Hery Pudjoprastyono (UNIVED Press, 2023)
Shopee is one of the most popular online marketplaces for consumers to purchase. The increase in online shopping during the COVID-19 pandemic can be attributed to impulse purchases driven by various factors, including more convenient shopping and discounts. This study uses a quantitative methodology and uses the variables